Herpes-associated erythema multiforme in a postmenopausal woman - Hendri Susanto; Nurhilailah Nurhilailah; Raziv Ganesha; Hening Tuti Hendarti; Priyo Hadi (Majalah Kedokteran Gigi Indonesia, 2021)
Herpes-associated erythema multiforme (HAEM) is an acute inflammatory mucocutaneous disease which is characterized by ulcerative lesion on oral mucous membrane with or without skin involvements. The etiology of erythema multiforme (EM) is probably hypersensitivity reaction to human herpes simplex virus tipe 1 (HSV-1). Lesions on lips with HAEM can be treated by corticosteroid and acyclovir topically and/or orally. The objective of this study wasto report the case of HAEM with painful ulcers accompanying with crust on lips. A 55 years old woman complained painful ulcers with crust on lips since the last five months. She had visited a primary health care service and received several medications such as antibiotic (ciprofloxacin), anti-inflammatory drug (corticosteroid), analgesic (mefenamic acid) but her complaint was never healed completely because it was always recurring. The lesion on her lips got worse when she ate hot and spicy food and after she went out for outdor activities. She had a history of herpes virus infection seven months before but it was completely healed after treated by acyclovir topically and amoxicilin orally. An extra oral examination found black brown crust on her upper lip vermillion, well-demarcated, irregular margin, rough surface, erythematous surrounding area, accompanied with pain. An intra oral examination identified ulcers, yellowish, 4-5 mm in size, well-demarcated, irregular margin, redness in surronding area, accompanied with pain. Acomplete blood count examination, serology test for HSV-1 (IgM and IgG) were taken and the result showed that only IgG was reactive. The therapies given to the patient were topical medications with a combination of corticosteroid, chloramphenicol and moisturizer, followed by methyl prednisolone and acyclovir orally. After 6-week treatment, the lesions were completely healed.Herpes-associated erythema multiforme (HAEM) caused by hypersensitivity reactionto herpes simplex virus type 1 (HSV-1) may have a characteristic of painful ulcers accompanied with crust on the lips. The combination of both anti-inflammatory and antiviral drugs can be a choice for the therapy.